Health Insurance Policy and Public Health Governance in Southeast Asia: A Bibliometric Perspective - Judijanto, Loso; Irmayanti, Irmayanti (West Science Social and Humanities Studies, 2025)
This study examines the progression of research regarding health insurance policy and public health governance in Southeast Asia by a bibliometric analysis of publications from 2000 to 2025. Data were obtained from Scopus and Web of Science and examined with VOSviewer and Biblioshiny to delineate authorship, institutional collaboration, topic structures, and keyword co-occurrence. The findings indicate that global research is primarily led by institutions from the United States, the United Kingdom, and Australia, with notable contributions emerging from Southeast Asia, specifically Indonesia, Malaysia, Thailand, and the Philippines. Central issues include public health, health care policy, health care expenditure, and health disparities prevail in the field, illustrating a synthesis of governance, equity, and health financing viewpoints. The research gives pragmatic insights for enhancing regional policy collaboration and contributes theoretically to the comprehension of knowledge diffusion and governance networks in public health. Notwithstanding database and linguistic constraints, the results highlight the increasing significance of Southeast Asia in influencing the global dialogue on universal health care and sustainable health governance.